Redescription and taxonomical considerations about Aonchotheca (Aonchotheca) pulchra n. comb. (Enoplida: Trichuridae), a nematode of Nyctinomops spp. - Cardia, Daniel Fontana Ferreira [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP]; Tebaldi, José Hairton [UNESP]; Fornazari, Felipe [UNESP]; Menozzi, Benedito Donizete [UNESP]; Langoni, Helio [UNESP]; Nascimento, Adjair Antônio do [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
Pterothominx pulchra (Freitas, 1934) are little known gastric nematodes of Nyctinomops laticaudatus (Chiroptera: Molossidae). Information about the occurrence and host range of these parasites in Neotropical region is still scanty, and the only two morphological descriptions available in the literature are divergent about the presence or absence of a spiny spicular sheath in males, which may lead to incorrect taxonomical positioning, since this feature represents the main difference between the genera Pterothominx and Aonchotheca. Based on the absence of this morphological feature in specimens of this nematode obtained from N. laticaudatus and Nyctinomops macrotis bats captured in two municipalities in the state of Sao Paulo, Brazil, the present study reclassifies the aforementioned species in the genus Aonchotheca and allocates it to the subgenus Aonchotheca. Additional morphometric data and new host and locality records are also provided.

Pterothominx pulchra (Freitas, 1934) são nematódeos gástricos pouco conhecidos de Nyctinomops laticaudatus (Chiroptera: Molossidae). Informações referentes à ocorrência e variedade de hospedeiros desses parasitos ainda são escassas na região Neotropical. As únicas duas descrições morfológicas disponíveis na literatura são divergentes entre si quanto à presença de bainha espicular espinhosa nos machos, o que resultou no posicionamento taxonômico equivocado desta espécie, uma vez que, é a principal característica para diagnóstico dos gêneros Pterothominx e Aonchotheca. Baseado na ausência dessa característica morfológica em espécimes desse nematódeo, obtidos em morcegos N. laticaudatus e Nyctinomops macrotis capturados em dois municípios do Estado de São Paulo, Brasil, o presente estudo classifica a referida espécie no gênero Aonchotheca e a aloca no subgênero Aonchotheca, além de fornecer dados morfométricos adicionais e novos registros de hospedeiro e localidades.
Redescrição e considerações taxonômicas sobre Aonchotheca (Aonchotheca) pulchra n. comb. (Enoplida: Trichuridae), um nematódeo de Nyctinomops spp.
Keywords: Nematoda; Capillariinae; Chiroptera; Molossidae; Taxonomy; Morphology; Nematoda; Capillariinae; Chiroptera; Molossidae; Taxonomia; Morfologia